2016
DOI: 10.1007/s00420-016-1145-3
|View full text |Cite
|
Sign up to set email alerts
|

Ambient and at-the-ear occupational noise exposure and serum lipid levels

Abstract: No associations between ambient or at-the-ear occupational noise exposure and serum lipid levels were observed. This indicates that a causal pathway between occupational and residential noise exposure and cardiovascular disease does not include alteration of lipid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…However, this relationship has been less consistently observed the literature than hypertension. Some studies found no association at all 11 and others found an association with only certain types of cholesterol, such as a lower HDL among those with bilateral high frequency hearing loss. 31…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this relationship has been less consistently observed the literature than hypertension. Some studies found no association at all 11 and others found an association with only certain types of cholesterol, such as a lower HDL among those with bilateral high frequency hearing loss. 31…”
Section: Discussionmentioning
confidence: 98%
“…810 However, research regarding associations with other manifestations of cardiovascular disease, such as elevated cholesterol and CHD, has been less consistent, with some studies finding no association. 11,12 Many studies assessing the association between occupational noise and cardiovascular conditions have suffered from small sample sizes, 13 inadequate control of important covariates such as BMI or socioeconomic satus, 14 or lack of generalizability due to being conducted in a single occupation or industry. 15 Additionally, most studies were conducted on workers outside of the United States.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…In a study of 144,082 participants aged ≥ 20 years, Cai et al [ 58 ] found higher daytime noise exposure was positively associated with higher triglycerides. Besides, one study found an association of occupational noise and increasing triglyceride levels [ 33 ]. Another study found the triglycerides of a group exposed to high industrial noise were significantly higher than a low-exposure group after adjustment for age, BMI, smoking and work hours per week [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found an association between long-term noise exposure and general obesity in women in Norway [ 32 ]. Arlien-Søborg et al [ 33 ] found that occupational noise exposure levels are strongly associated with increasing levels of triglycerides and cholesterol HDL ratio, and a decreasing level of HDL cholesterol. In addition, higher exposure to black carbon (a marker of traffic-related pollution) has been shown to be significantly associated with low HDL cholesterol [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, dyslipidemia has not been confirmed by others [ 4 , 16 , 17 ]. A study manifested no association between occupational noise exposure and dyslipidemia, although adjusted for 11 confounding factors such as sex, age, and body mass index (BMI) [ 18 ]. In addition, the effect of noise on blood lipids needed to be accumulated over a long period of time, but few studies explored the relationship between noise exposure years and blood lipids.…”
Section: Introductionmentioning
confidence: 99%